Effects of Organic Acid Addition on Fruiting Productivity and Primordium Formation in Grifola frondosa - Jeong-Han Kim; Myoung-Jun Jang (한국균학회지, 2019)
This study was performed to develop a useful method for substrate pH adjustment in bottle cultivation of Grifola frondosa. Four types of organic acid solution—citric acid, malic acid, tartaric acid, and succinic acid—were added at 0.5% to 3.0% (w/v) into the substrate. The pH after the organic acid treatments ranged from 3.8 to 4.8 for the mycelial growth of G. frondosa after sterilization. Supplementation with succinic acid at 0.5% resulted in a shorter cultivation period and higher consistent yields compared to other organic acid treatments. These results indicate that the technique we developed is beneficial for higher production of G. frondosa using bottle cultivation.